Analisis Keterampilan Berpikir Tingkat Tinggi Pada Pembelajaran Bahasa Indonesia Di Kelas V UPT SPF SD Negeri Labuang Baji 1 Kota Makassar - Rezky Andiny; Munirah; Anin Asnidar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze teacher planning, learning implementation, and students' higher-order thinking skills (HOTS) in Indonesian language learning for fifth graders at the SPF Technical Implementation Unit (UPT SPF) of Labuang Baji 1 Elementary School in Makassar City. The study used a descriptive qualitative approach with fifth-grade teachers and students as subjects. Data were collected through lesson plan analysis, learning observations, daily evaluation tests, and interviews, then analyzed through data reduction, data presentation, and conclusion drawing. The results of the analysis indicate that the learning plan has fulfilled the 2013 Curriculum requirements administratively, but is still dominated by lower-order thinking indicators, thus not optimally developing students' HOTS. The learning implementation runs well and actively involves students, but learning activities and questions still focus on factual aspects and understanding. The evaluation instrument is dominated by LOTS questions at 70% and HOTS at 30%, with student achievement in the LOTS category being good and in the HOTS category being sufficient. These findings indicate that students' higher-order thinking skills still need to be strengthened through more HOTS-oriented learning planning, implementation, and assessment.